Antibacterial activity of the sediment of copper removal from wastewater by using mechanically activated calcium carbonate. (1st December 2018) - Zhang, Tingting; Wen, Tong; Zhao, Yunliang; Hu, Huimin; Xiong, Bowen; Zhang, Qiwu
Abstract: Recently the focus of research interest has changed from merely purification of wastewater to the recovery of the heavy metals inside and even direct utilization of the obtained heavy metal product as functional materials. In this work, the method of mechanically activated CaCO3 was used for copper removal from wastewater. The removal rate reached as high as 99.9% even with the Ca/Cu molar ratio of 1.0 and the residual copper concentration was less than 0.5 mg/L (initial concentration 300 mg/L), meeting the discharge standard. The sediment was characterized by XRD, TG-DSC and SEM-EDS respectively. Posnjakite (Cu4 (SO4 )(OH)6 H2 O) was found as the main product in the sediment of copper removal. Bactericidal experiments of two well known species of bacteria, Escherichia coli and Staphylococcus aureus, confirmed excellent antibacterial activity of the sediment, via direct contact with bacteria rather than released copper ions, therefore, the high potential of the sediment to serve as copper-based antibacterial agent. This novelly proposed concept using the sediment from the wastewater treatment as an antibacterial agent opens a new direction for the research in environmental field. Graphical abstract: Image Highlights: New concept using sediment from copper wastewater treatment as antibacterial agent. Mechanically activated CaCO3 presents high efficiency of copper removal. Posnjakite (Cu4 (SO4 )(OH)6 H2 O) was found as the main product in the sediment. Sediment shows excellent antibacterial activity to both E. coli and S. aureus.